Pengaruh Pendapatan, Lifestyle Hedonis, dan Kebiasaan Belanja Online Terhadap Pengelolaan Keuangan Pribadi: Studi Kasus pada Masyarakat Kampung Kabayan, Cileles, Lebak, Banten - Ridwan Fauzi; Lutfi Alhazami (Teewan Journal Solutions, 2026)
This study aims to examine the influence of income, hedonic lifestyle, and online shopping habits on the personal financial management of the people of Kabayan Village, Cileles, Lebak, Banten, with a focus on how these three factors affect an individual's ability to manage finances effectively. Using a quantitative approach and survey method, a population of 133, using the Slovin formula with a margin of error of 5% and a non-probability sampling technique, a sample of 100 people was obtained, data were collected through questionnaires. The analysis was carried out using multiple linear regression with the help of SPSS 26 software. The results showed that income (X1) had a significant effect on financial management, with a calculated t value of 2.587> t table 1.985 and a sig. value of 0.011 <0.05; Hedonic lifestyle (X2) also had a significant effect on personal financial management with a calculated t value of 2.241> t table 1.985 and a sig. value of 0.027 <0.05; Online shopping habits (X3) have the most dominant influence with a calculated t value of 5.176 > t table 1.985 and a sig. value of 0.000 < 0.05; Simultaneously, the three variables show a significant influence on personal financial management with a calculated F value of 62.191 > F table 2.70 and a sig. value of 0.000 < 0.05, with a coefficient of determination (R²) of 0.660, meaning that 66% of the variation in financial management is explained by these three factors, while 34% is influenced by other variables outside the model.